Upstream AUGs in embryonic proinsulin mRNA control its low translation level - Hernández‐Sánchez, Catalina; Mansilla, Alicia; Pollerberg, G. Elizabeth (The EMBO journal, 2003)
Proinsulin is expressed prior to development of the pancreas and promotes cell survival. Here we study the mechanism affecting the translation efficiency of a specific embryonic proinsulin mRNA. This transcript shares the coding region with the pancreatic form, but presents a 32 nt extended leader region. Translation of proinsulin is markedly reduced by the presence of two upstream AUGs within the 5′ extension of the embryonic mRNA. This attenuation is lost when the two upstream AUGs are mutated to AAG, leading to translational efficiency similar to that of the pancreatic mRNA. The upstream AUGs are recognized as initiator codons, because expression of upstream ORF is detectable from the embryonic transcript, but not from the mutated or the pancreatic mRNAs. Strict regulation of proinsulin biosynthesis appears to be necessary, since exogenous proinsulin added to embryos in ovo decreased apoptosis and generated abnormal developmental traits. A novel mechanism for low level proinsulin expression thus relies on upstream AUGs within a specific form of embryonic proinsulin mRNA, emphasizing its importance as a tightly regulated developmental signal.